DIAGNOSIS OF RELAY-CONTACT DEVICES OF RAILWAY AUTOMATICS - Havryliuk, V. I.; Dub, V. Yu. (Science and Transport Progress, 2006)
The analysis of existing methods of construction of diagnostic tests of discrete devices is carried out, algorithms and the program of construction of checking and diagnostic tests for the relay-contact equipment of railway automatics are developed.